Hubungan Pengetahuan dan Sikap tentang Personal Hygiene dengan Penatalaksanaan Kebersihan Genetalia Saat Menstruasi pada Remaja Putri - Shafara Nabila; Dwi Yunita Rahmadhani; Zafrullah Zein (3031-8572, 2022)
Personal hygiene is one of the steps undertaken to preserve a person's cleanliness, health, and well-being, both physical and psychological. Health, personal hygiene, and disease prevention get enhanced on a whole. Personal hygiene awareness will influence personal hygiene habits. This investigation is to see the relationship between knowledge, attitudes, and personal hygiene in young women at Stated Junior High School 22 in Jambi City and the management of genital hygiene during menstruation.It is a quantitative study using a cross-sectional design. The participants in this study were students from Stated Junior High School 22 in Jambi City who had menstruated. This research comprised 40 female students as participants and employed Spearman Brown rank correlation and stratified random sampling analysis.The findings of this study were acknowledged by 40 respondents, with an average of 60.50 for knowledge, 64.45 for attitudes, and 69.67 for personal hygiene behaviour. With a bivariate value equal 0.002 for knowledge and 0.011 for attitude, it can be inferred that knowledge and attitudes are linked to the management of personal hygiene and hygiene genetalia during menstruation. The study discovered a relationship between knowledge and knowledge about personal cleanliness and the application of genetalia testing during menstruation at Stated Junior High School number 22 in Jambi.